The effect of interactive learning methods and reflection on nurses’ learning in patient safety at the ICU and Emergency department - Samaneh Mirzaei; Fatemeh Keshmiri; Roohangiz Norouzinia; Najmeh Mirjalili; Naeimeh Baghshahi; Mohsen Gholinataj Jelodar (BMC Health Services Research)
Abstract Introduction Patient safety is vital to health care delivery and service quality. Therefore, it should be a priority in every healthcare system worldwide. As the importance of patient safety is increasingly recognized, the emphasis on training and its impact on safety competencies and quality of care has also grown. Innovation in education is essential to keep pace with the growing need to enhance patient safety through an effective education program. Therefore, this study was conducted to compare the effectiveness of the patient safety education program in Case-based Learning (CBL), lectures, and reflection on the knowledge, attitude, and performance of patient safety in the nurses of the Intensive care unit (ICU) and emergency department of Shahid Rahnemoon Hospital, Yazd. Method The quasi-experimental study was conducted by the nurses of the intensive care unit and emergency departments of Shahid Rahnamoon Teaching Hospital, Yazd, Iran, from November 2023 to the end of April 2024, using a three-group quasi-experimental intervention design with a pre and post-test. Nurses were randomly divided into three teaching groups: lecture, case-based learning, and reflection. The knowledge, attitude, and patient safety performance questionnaires were used before and three months after the intervention. Results In this study, 113 nurses were analyzed across three groups: Case-Based Learning (CBL) with 38 participants, reflection with 38 participants, and lecture with 37 participants. The mean scores for knowledge pre- and post-study in the three groups were as follows: CBL (4.81 ± 1.24 vs. 8.07 ± 1.36), reflection (4.94 ± 1.39 vs. 8.18 ± 1.44), and lecture (5.16 ± 1.42 vs. 7.75 ± 1.40). Similarly, the average scores for attitude pre- and post-study were recorded as: CBL (41.50 ± 4.89 vs. 54.68 ± 4.64), reflection (41.23 ± 6.22 vs. 49.94 ± 6.42), and lecture (41.37 ± 6.75 vs. 48.62 ± 5.64). For practice, the average scores pre- and post-study were CBL (3.44 ± 1.05 vs. 6.26 ± 1.22), reflection (3.55 ± 1.08 vs. 5.76 ± 1.58), and lecture (3.59 ± 1.06 vs. 5.13 ± 1.53). These results indicate overall knowledge, attitude, and practice improvement across all groups following the study. Before the study, there were no significant differences in knowledge (F = 0.621, p = 0.539), attitude (F = 0.018, p = 0.982), and practice (F = 0.19, p = 0.828) among the three groups. After the study, no significant difference was found in knowledge (F = 0.938, p = 0.394); however, a significant difference was observed in attitude (F = 12.13, p < 0.0001) and practice (F = 506, p = 0.005). Conclusion According to the study's findings, all three groups of nurses demonstrated significantly higher scores in knowledge, attitudes, and performance after the intervention compared to before. However, no significant difference was observed among the three groups in the area of knowledge. Nonetheless, case-based learning significantly improved the average scores for attitudes and performance. These results indicate that patient safety training programs effectively enhance nurses' knowledge.